DEVELOPMENT OF PERFORMANCE SKILLS OF GYMNASTS IN GYMNASTICS (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
The article considers the turns of the spiral, along which the development and growth of the technical skills of athletes takes place, leading to an increase in the quality of the performance of competitive programs. Quality is always understood as strict compliance with the technical standards of the reference technique of elements and combinations.